Biochar for agricultural soil carbon sequestration and CO2 mitigation: a bibliometric analysis of research hotspots, gaps and climate-resilient pathways - Qi Wei; Qi Wei; Junzeng Xu; Peng Chen; Ziwei Li; Zhiming Qi (Applied Soil Ecology, 2026)

Water Quality Impact on Fish Behavior: A Review From an Aquaculture Perspective - Kaisheng Zhang; Zhangying Ye; Ming Qi; Wenlong Cai; João L. Saraiva; Yanci Wen; Gang Liu; Ze Zhu; Songming Zhu; Jian Zhao (Reviews in Aquaculture, 2025)
Changes in water quality significantly shape fish behavior, a crucial index reflecting the growth and welfare status of fish. Given the centrality of this relationship to aquaculture practices, a comprehensive understanding of how water quality dynamics influence fish behavior is imperative. While there have been some summaries of the effects of water quality parameters on fish physiology and growth, few reviews on their effects on fish behavior have been reported yet. This article reviews several water quality parameters which are of great concern in aquaculture from multiple facets of actual production, including physical parameters (water temperature and turbidity), chemical parameters (dissolved oxygen, salinity, pH, and inorganic nitrogen), and chemical pollutants (microplastics and crude oil), which have gained increasing attention from the researchers and aquaculture practitioners over the past decades. Variations in these water quality parameters can exert profound effects on fish physiology, metabolism, internal tissues and organs, and sensory perception, which influences fish behaviors such as swimming, schooling, feeding, predation, anti‐predation, aggression, courtship, as well as adaptive and stress‐related behaviors such as exploration, avoidance response, and anxiety‐like behavior. By synthesizing the behavioral changes caused by specific water quality parameters, this review aims to provide strong support for further water quality‐related research, thereby fostering environments conducive to both fish welfare and aquaculture productivity.

Simulation of evapotranspiration and yield of maize: An inter-comparison among 41 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2023)